Defective neutrophil chemotaxis and raised serum ige levels in a child with recurrent bacterial infections and eczema. Influence of levamisole. Issue 2 (February 1978) - De Cree, J; Emmery, L; Timmermans, J; Eeckels, R; De Cock, W; Verhaegen, H
Abstract : A 5 1/2-year-old girl, with a life-long history of recurrent staphylococcal infections and eczematous dermatitis had a defect in polymorphonuclear leucocyte chemotaxis and phagocytosis in autologous serum, a high serum IgE level, and a disturbed T cell function. Levamisole improved all the immunological abnormalities and there was a dramatic clinical improvement. Discontinuation of therapy with levamisole resulted in gradual deterioration.